A gut microbiota-independent mechanism shapes the bile acid pool in mice with MASH - Justine Gillard; Martin Roumain; Corinne Picalausa; Morgane M. Thibaut; Laure-Alix Clerbaux; Anne Tailleux; Bart Staels; Giulio G. Muccioli; Laure B. Bindels; Isabelle A. Leclercq (JHEP Reports)
Background & Aims: An imbalance between primary and secondary bile acids contributes to the development of metabolic dysfunction-associated steatohepatitis (MASH). The precise mechanisms underlying changes in the bile acid pool in MASH remain to be identified. As gut bacteria convert primary bile acids to secondary bile acids, we investigated the contribution of the gut microbiota and its metabolizing activities to bile acid alterations in MASH. Methods: To disentangle the influence of MASH from environmental and dietary factors, high-fat diet fed foz/foz mice were compared with their high-fat diet fed wildtype littermates. We developed functional assays (stable isotope labeling and in vitro experiments) to extend the analyses beyond a mere study of gut microbiota composition (16S rRNA gene sequencing). Key findings were confirmed in C57BL/6J mice were fed a Western and high-fructose diet, as an independent mouse model of MASH. Results: Although mice with MASH exhibited lower levels of secondary 7α-dehydroxylated bile acids (3.5-fold lower, p = 0.0008), the gut microbial composition was similar in mice with and without MASH. Similar gut microbial bile salt hydrolase and 7α-dehydroxylating activities could not explain the low levels of secondary 7α-dehydroxylated bile acids. Furthermore, the 7α-dehydroxylating activity was unaffected by Clostridium scindens administration in mice with a non-standardized gut microbiota. By exploring alternative mechanisms, we identified an increased bile acid 7α-rehydroxylation mediated by liver CYP2A12 and CYP2A22 enzymes (4.0-fold higher, p <0.0001), that reduces secondary 7α-dehydroxylated bile acid levels in MASH. Conclusions: This study reveals a gut microbiota-independent mechanism that alters the level of secondary bile acids and contributes to the development of MASH in mice. Impact and implications:: Although changes in bile acid levels are implicated in the development of metabolic dysfunction-associated steatohepatitis (MASH), the precise mechanisms underpinning these alterations remain elusive. In this study, we investigated the mechanisms responsible for the changes in bile acid levels in mouse models of MASH. Our results support that neither the composition nor the metabolic activity of the gut microbiota can account for the alterations in the bile acid pool. Instead, we identified hepatic 7α-rehydroxylation of secondary bile acids as a gut microbiota-independent factor contributing to the reduced levels of secondary bile acids in mice with MASH. Further investigation is warranted to understand bile acid metabolism and its physiological implications in clinical MASH. Nonetheless, our findings hold promise for exploring novel therapeutic interventions for MASH.